Pencegahan Stunting dengan Kelas Calon Pengantin (KEPITING DIKECAPIN): Preventing Stunting with Premarital Clases (KEPITING DIKECAPIN) - Zuhana, Nina; Prafitri, Lia Dwi; Supriatinah, Lusy (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Stunting is a chronic nutritional problem that needs to be prevented from the preconception period onward, as it is associated with long-term nutritional deficiencies and high rates of recurrent infections in children, particularly during the critical first 1,000 days of life. The "Kepiting Dikecapin" community service program was designed to strengthen stunting prevention efforts among prospective brides and grooms through a series of interventions, including nutritional status assessments (BMI and hemoglobin), pre-marital stunting prevention education, reproductive health counseling, and a demonstration of making corn milk as an example of nutritious local food. The program was implemented over approximately six months, from March to August 2025, through a sequence of structured activities that included initial socialization (FGD 1), pre-marital classes, understanding assessments, and the development of follow-up plans. Implementation took place in seven community health centers (puskesmas) with the highest stunting prevalence among a total of sixteen health centers in the Pekalongan District Health Office’s working area. The results show a significant increase in knowledge, with the average pre-test score of 70.63 rising to 90.41 in the post-test after the educational materials were delivered. These findings highlight the effectiveness of the integrated educational approach in improving prospective couples’ understanding of stunting prevention. The program has the potential to serve as a preconception intervention model, better preparing couples to build healthy families and support the development of an optimally growing future generation.